The in vitro effects of isoflurane, sevoflurane, and propofol on platelet aggregation - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1999)
We studied the in vitro effects of sevoflurane, isoflurane, and propofol anesthesia on platelet function. Thirty patients undergoing minor surgical procedures were divided into three groups (n = 10 each). Induction of anesthesia was achieved by using 5 mg/kg thiopental TV, and 0.1 mg/kg vecuronium TV was used for muscle relaxation. Anesthesia maintenance was provided by sevoflurane in the first, isoflurane in the second, and propofol infusion in the third group with 70% N2O in O-2. Hemoglobin, hematocrit, thrombocyte count, prothrombin time, activated partial thromboplastin time, international normalized ratio, arterial pH, von Willebrand factor, viscosity, platelet aggregation, and bleeding time were measured 1 h pre-, intra-, and postanesthesia. There was no difference among the platelet aggregation ratios of the pre-, intra-, and postoperative periods in the isoflurane group. The aggregation ratios in the sevoflurane and propofol groups were significantly reduced at intraoperative periods compared with preoperative values. Diminished aggregation values were also found Ih postoperatively compared with the control values in the sevoflurane and propofol groups. We conclude that, in patients with a bleeding tendency during the intra- and early postoperative period, isoflurane may be preferred as a general anesthetic. Implications: In our study, using vacuum-operated tubes, we demonstrated that sevoflurane and propofol had a significant inhibitory effect on intraoperative and early postoperative platelet aggregation, whereas isoflurane had no effect. Therefore, isoflurane may be preferred as a general anesthetic in patients with a clinically relevant bleeding tendency.
Keywords: ANESTHETICS